Fetal whole‐heart 4D imaging using motion‐corrected multi‐planar real‐time MRI. Issue 3 (12th May 2019) - van Amerom, Joshua F.P.; Lloyd, David F.A.; Deprez, Maria; Price, Anthony N.; Malik, Shaihan J.; Pushparajah, Kuberan; van Poppel, Milou P.M.; Rutherford, Mary A.; Razavi, Reza; Hajnal, Joseph V
Abstract : Purpose: To develop an MRI acquisition and reconstruction framework for volumetric cine visualization of the fetal heart and great vessels in the presence of maternal and fetal motion. Methods: Four‐dimensional (4D) depiction was achieved using a highly‐accelerated multi‐planar real‐time balanced steady‐state free precession acquisition combined with retrospective image‐domain techniques for motion correction, cardiac synchronization and outlier rejection. The framework was validated using a numerical phantom and evaluated in a study of 20 mid‐ to late‐gestational age human fetal subjects (23‐33 weeks gestational age). Reconstructed MR data were compared with matched ultrasound. A preliminary assessment of flow‐sensitive reconstruction using the velocity information encoded in the phase of real‐time images is included. Results: Reconstructed 4D data could be visualized in any two‐dimensional plane without the need for highly specific scan plane prescription prior to acquisition or for maternal breath hold to minimize motion. Reconstruction was fully automated aside from user‐specified masks of the fetal heart and chest. The framework proved robust when applied to fetal data and simulations confirmed that spatial and temporal features could be reliably recovered. Evaluation suggested the reconstructed framework has the potential to be used for comprehensive assessment of the fetal heart, either as an adjunct to ultrasound or in combination with other MRI techniques. Conclusions: The proposed methods show promise as a framework for motion‐compensated 4D assessment of the fetal heart and great vessels.